QUARANTINE TREATMENT OF FRUIT FLY BACTROCERA CORRECTA INFESTED IN NAMROI POLEMO BY GAMMA RADIATION AT HANOI IRRADIATION CENTER - NGUYEN , VAN BINH; TRAN , BANG DIEP; PHAM , DUY DUONG; HOANG , PHUONG THAO; NGUYEN , THANH HIEN; VU , THI THUY; TRAN , MINH QUYNH (Nuclear Science and Technology, 2012)
In this study, gamma irradiation was applied as an effective tool for quarantine treatment of fruit fly Bactrocera correcta existing on Nam Roi pomelos. The fruits were infected with eggs and larva of the fruit fly and irradiated by Cobalt-60 gamma source. The effects of gamma radiation on egg hatching, larval survival, pupation rate, adult emergence of this fruit fly were investigated. Results showed that the radiation dose of 250Gy is enough for this purpose. Though small amount of survived larva can develop into pupa, the emergence rate is in inverse ratio to radiation dose and no adult fruit fly could be observed. The results also revealed that the sensory and nutrient quality of irradiated grape fruits were not affected by irradiation with the doses upto 850Gy. There are no difference in the contents of total sugar and vitamin C between the treated and control fruits. In conclusion, the gamma radiation of 250Gy can be applied to quarantine treatment of Bactrocera correcta infected on Nam Roi pomelos.